THE EFFECTIVENESS OF CINEMATHERAPY TECHNIQUE GROUP GUIDANCE IN PREVENTING STUDENT SEXUAL HARASSMENT - Suryati, Suryati; Dewi, Emi Puspita; Ramadhayanti, Agnesia (Jurnal Konseling Pendidikan Islam, 2025)
The purpose of this study was to determine the effectiveness of the cinematherapy technique group guidance in preventing sexual harassment of students at Madrasah Aliyah Ar Rahman Palembang. The design used in this study was quasi-experimental. The sample of this study was 20 students who were divided into 2 groups. The results of the study showed a significant difference between the experimental group and the control group. The posttest results of the experimental group were 49.2, while the posttest of the control group was 45.3. The results of the t-test in the pretest and posttest experimental groups showed that the significance was not reached. 0.000 < 0.05, which means Ha is accepted. It can be concluded that the provision of cinematherapy technique group guidance services is effective in preventing sexual harassment among students of MA Ar Rahman Palembang.